Endometrial and Menstrual Blood Mesenchymal Stem/Stromal Cells: Biological Properties and Clinical Application - Bozorgmehr, Mahmood; Gurung, Shanti; Darzi, Saeedeh; Nikoo, Shohreh; Kazemnejad, Somaieh; Zarnani, Amir-Hassan; Gargett, Caroline E. (Frontiers in Cell and Developmental Biology, 2020)
A highly proliferative mesenchymal stem/stromal cell (MSC) population was recently discovered in the dynamic, cyclically regenerating human endometrium as clonogenic stromal cells that fulfilled the International Society for Cellular Therapy (ISCT) criteria. Specific surface markers enriching for clonogenic endometrial MSC (eMSC), CD140b and CD146 co-expression, and the single marker SUSD2, showed their perivascular identity in the endometrium, including the layer which sheds during menstruation. Indeed, cells with MSC properties have been identified in menstrual fluid and commonly termed menstrual blood stem/stromal cells (MenSC). MenSC are generally retrieved from menstrual fluid as plastic adherent cells, similar to bone marrow MSC (bmMSC). While eMSC and MenSC share several biological features with bmMSC, they also show some differences in immunophenotype, proliferation and differentiation capacities. Here we review the phenotype and functions of eMSC and MenSC, with a focus on recent studies. Similar to other MSC, eMSC and MenSC exert immunomodulatory and anti-inflammatory impacts on key cells of the innate and adaptive immune system. These include macrophages, T cells and NK cells, both in vitro and in small and large animal models. These properties suggest eMSC and MenSC as additional sources of MSC for cell therapies in regenerative medicine as well as immune-mediated disorders and inflammatory diseases. Their easy acquisition via an office-based biopsy or collected from menstrual effluent makes eMSC and MenSC attractive sources of MSC for clinical applications. In preparation for clinical translation, a serum-free culture protocol was established for eMSC which includes a small molecule TGFβ receptor inhibitor that prevents spontaneous differentiation, apoptosis, senescence, maintains the clonogenic SUSD2+ population and enhances their potency, suggesting potential for cell-therapies and regenerative medicine. However, standardization of MenSC isolation protocols and culture conditions are major issues requiring further research to maximize their potential for clinical application. Future research will also address crucial safety aspects of eMSC and MenSC to ensure these protocols produce cell products free from tumorigenicity and toxicity. Although a wealth of data on the biological properties of eMSC and MenSC has recently been published, it will be important to address their mechanism of action in preclinical models of human disease.